Networks and institutions in Europe's emerging markets - Schoenman, Roger (Cambridge Studies in Comparative Politics, 2014)
Do ties between political parties and businesses harm or beneﬁt the development of market institutions? The post-communist transition offers an unparalleled opportunity to explore when and how networks linking the polity and the economy support the development of func-tional institutions. A quantitative and qualitative analysis covering eleven post-socialist countries combined with detailed case studies of Bulgaria, Poland, and Romania documents how the most successful post-communist countries are those in which dense networks link polit-icians and businesspeople, as long as politicians are constrained by intense political competition. The comparison of original network data sets shows how this combination allowed Poland to emerge with stable institutions. Bulgaria, marred by weak institutions, corruption, and violence, cautions us that in developing economies intense political competition alone is harmful in the absence of dense personal and ownership networks. Indeed, as Romania illustrates, networks are so critical that their weakness is not mitigated even by low political competition. This title was made Open Access by libraries from around the world through Knowledge Unlatched.